Análise de distribuição espacial de transtornos mentais no Brasil - MAIA, Luiz Artur Barbosa (2023)
The issue of mental disorders in the country is a real concern, which requires spatial analysis to know how the problem is distributed across the country and geographically analyzing how factors that lead to this behave are effective ways of finding answers and acquiring understanding and information about the subject. Based on this principle, the elaboration of the present study aims to analyze the spatial distribution of mental disorders in Brazil, following factorial concepts that influence the problem, correlating and bringing to light the importance of environmental issues that are part of mental health issues, for the well-being of the Brazilian people. From this point of view, the concept of social geographical formation brings, through a cultural prism, explanations of the reason for the urban territorial organization and the problems that compose it. Geoprocessing and data analysis techniques were used with programming language, with spatial data from the year 2019 for the production of graphs and thematic maps that compare results between the states with the highest and lowest record of mental disorders, urban formations, temporal analyzes of social data and environmental preservation, which illustrate and facilitate the analysis of the problem. It is important to note the original character of this work, the possibility of developing more studies and the importance in relation to this area of study, because unlike what is seen in the area of health geography, there is little use of geoprocessing for spatial analysis of mental disorders specifically.